Design of low voltage micropower asynchronous datapath modules for a multiplierless FIR filter - Chua, Chien Chung. (2008)
In this dissertation, we propose three novel low power 16-bit circuit modules for the datapath of an FIR filter: (i) Multiplierless-based Multiplier, (ii) 2's-Complement-In-Sign-Magnitude-Out Adder, and (iii) Latch Accumulator.